Implementation Of E-Learning to Improve Motivation and Learning Outcomes in Class XI Multimedia Students in Creative Entrepreneurship Products Design Subject - Damanja, Muhammad Ikhsan (Jurnal Guru Komputer, 2022)
The rapid technological progress had an impact on all aspects of life related to the world of information and technology, including education. Following the pandemic COVID-19, the use of the internet and e-learning had become widespread, and which purpose is to substitute offline class activity. This study aims to determine the increase in student learning outcomes after being given treatment with E-Learning models on the subject of Entrepreneurial Creative Products Design. This research was conducted in one of the SMK Negeri 2 Bandung. The method used in this study is quantitative method and the model used is cooperative learning. The class activity is observed and divided into 2 cycles to ensure the continuous effect of E-learning. The results of the classroom action research carried out had an increase in learning outcomes by 31.4% based on their average scores. There is also an increase in student activeness by 17%. The result shows that E-learning is effective to be implemented in class